Analisis Kesulitan Pembelajaran Daring dengan Google Classroom dan Zoom Terhadap Hasil Belajar - Awaludin Fitra (Jurnal Pendidikan Matematika (JPM), 2022)
Penelitian ini merupakan penelitian eksperimen semu dengan desain kelompok membandingkan, menganalisis kesulitan dalam pembelajaran online, serta meninjau berbagai artikel sumber literatur. Subjek dalam penelitian ini adalah kelas eksperimen I yaitu kelas 3/TI/A2/02 yang berjumlah 22 orang, dan kelas eksperimen II yaitu kelas 3/TI/B/02 yang berjumlah 23 orang. Hasil analisis statistik dengan uji-t menghasilkan P Value sebesar 0,00156, dengan taraf signifikansi 0,05. H0 ditolak karena P Value lebih kecil dari 0,005, tetapi Ha diterima karena P Value lebih besar dari 0,005. Terakhir, terdapat perbedaan hasil pembelajaran online dengan Google Classroom dan Zoom yang berbantuan video dengan pembelajaran online dengan Google Classroom dan Zoom. Rata-rata hasil belajar online yang diperoleh dari Google Classroom dan ZoomÂ  yang berbantuan Video lebih tinggi dibandingkan yang diperoleh dari Pembelajaran online dengan Google Classroom dan Zoom. Mahasiswa memaparkan kesulitan-kesulitan berikut selama proses pembelajaran online: kepemilikan kuota internet yang terbatas menjadi penghambat pembelajaran online sebesar 67%, gangguan jaringan internet sebesar 18%, dan terjadinya pemadaman listrik saat pembelajaran online terjadi adalah 15%.Â This type of research is a quasi-experimental research with the design of comparing groups, analyzing difficulties and analyzing difficulties in online learning as well as reviewing various literature source articles. The subjects in this study were the experimental class I, namely class 3/TI/A2/02 consisting of 22 people and the experimental class II, namely 3/TI/B/02 consisting of 23 people. From the results of statistical analysis with t-test obtained P Value = 0.00156, with a significant level = 0.05. Because the P Value is less than 0.005, then H0 is rejected and Ha is accepted. In conclusion, there are differences in the results of online learning with Google Classroom and Video-assisted Zoom with online learning with Google Classroom and Zoom. the average online learning results obtained that online learning with Google Classroom and Video-assisted Zoom is higher than online learning with Google Classroom and Zoom. The difficulties experienced by students during the online learning process are: Limited ownership of internet quota is an obstacle in online learning by 67%, internet network disturbances by 18%, and the occurrence of power outages or blackouts when online learning takes place by 15%. using video is 3.77 (good) material aspects, compatibility aspects 3.59 (good), complexity 3.38 (sufficient), triability aspects 3.51 (good) and usefulness aspects 3, 6 (good). With this video-based learning an effort to provide material in the form of video tutorials practicing data analysis with Spss in statistics courses.Â